PENGEMBANGAN MEDIA VIDEO NARASI ANIMASI PADA MATERI BANGUN RUANG UNTUK SISWA KELAS IV SD MUHAMMADIYAH PAJANGAN 2 - Bara, Hengkang; Darmawan, Rizal Gilang (Universitas Veteran Bangun Nusantara, 2024)
The background to the problem of this research is the lack of interest of students in the subject of spatial mathematics in class IV elementary school. The aim of this research is to develop, determine the quality and effectiveness of spatial animation narrative videos as an effort to support the learning process for fourth grade elementary school students. The type of research used in this research is Research and Development (R&D) or better known as development research. The development model used in this research is 4-D. The 4-D development model consists of 4 main stages, namely: Define, Design, Develop and Disseminate. This method and model was chosen because it aims to produce products in the form of animated video media. The product trial was carried out at SD Muhammadiyah Pajangan 2 with a total of 21 students. The data analysis technique for this research was quantitative descriptive and qualitative descriptive techniques. The quantitative descriptive data analysis technique in this research is the results of assessments by experts, educators and students. The qualitative descriptive data analysis technique in this research takes the form of suggestions and criticism from experts, educators and students. Based on research conducted by researchers, the results were 81.9, so the results of the trial on class IV students were in the